2008
DOI: 10.1016/j.mambio.2007.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Diet of some species of Neotropical small mammals

Abstract: Dietary analysis was performed to determine the variations in diet of some small neotropical species of mammals collected in seasonal areas of the cerrado (a savannah-like grassland) and semi-deciduous forest. Food items were determined based on the analysis of stomach contents of 126 animals (one didelphid and five sigmodontine rodent species). Most species presented herbivorous-omnivorous habits, with a preference for the vegetative parts of plants. Akodon montensis Thomas (1913) was the most abundant speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
13

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 19 publications
2
21
0
13
Order By: Relevance
“…Montane grass mice (Akodon montensis; body mass: 37.4±3.4 g) are omnivorous cricetid rodents, but their diet consists primarily of plant material (Talamoni et al, 2008). They were captured during the rainy season between October and November 2012 in the Mata do São José (a remnant intact forest 15 km northeast of Rio Claro, São Paulo, Brazil).…”
Section: Animalsmentioning
confidence: 99%
“…Montane grass mice (Akodon montensis; body mass: 37.4±3.4 g) are omnivorous cricetid rodents, but their diet consists primarily of plant material (Talamoni et al, 2008). They were captured during the rainy season between October and November 2012 in the Mata do São José (a remnant intact forest 15 km northeast of Rio Claro, São Paulo, Brazil).…”
Section: Animalsmentioning
confidence: 99%
“…These authors concluded that, over the medium term, fire would favor plants with smaller seeds, facilitating their predation by smallbodied species such as mammals. Barlow & Peres (2003) observed a reduction in medium-and large-bodied vertebrates in burned areas, which would lead to a reduction in competition for food, favoring an increase in frugivorous-insectivorous species such as small mammals (Talamoni et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Estes itens foram considerados devido a sua maior importância na dieta destes animais (p. ex. Leite et al, 1996;Vieira et al, 2006;Iob e Vieira, 2008;Talamoni et al, 2008;Pinotti et al, 2011;Paglia et al, 2012). O levantamento da disponibilidade de recursos alimentares foi feito paralelamente à amostragem dos pequenos mamíferos.…”
Section: Disponibilidade De Recursos Alimentaresunclassified